Requests for Cancer Prevention Information: The Cancer Information Service (2002–2006) - Sullivan, Helen W. (2010)
BACKGROUND: Prevention is crucial to reducing cancer burden. Awareness of prevention information is critical to engaging the public in prevention activities. METHODS: We examined 106,610 information requests from the general public to the Cancer Information Service from 2002 to 2006. RESULTS: The percent of requests related to primary prevention decreased in 2003, but otherwise remained stable around 19%. The percent of requests related to secondary prevention decreased over time, from 38% (2003) to 14% (2006). Demographic characteristics were associated with patterns of change across time. CONCLUSIONS: Results suggest that efforts are needed to increase public awareness of cancer prevention, particularly among certain populations.